Experiences With Intravenous Thrombolysis in Acute Ischemic Stroke by Elderly Patients–A “Real World Scenario” - Héja, Máté; Fekete, István; Horváth, László; Márton, Sándor; Fekete, Klára Edit (Frontiers in Neurology, 2021)
Objectives: This retrospective single-centre study aimed to investigate the risk factors, outcomes and complication rates in patients older versus younger than 80 years treated with intravenous alteplase. Methods: Data of 1253 thrombolysed patients were analyzed between January 1, 2004 and August 31, 2016. Vascular risk factors, stroke severity based on the NIHSS score, functional outcome using modified Rankin Scale (mRS), mortality and symptomatic intracerebral hemorrhage (SICH) were compared between two subgroups (<80 and ≥80 years). Results: 1125 patients were included, 199 (17.6%) among them were aged over 80 years, majority (63.3%) were female (p<0.00001). Mean age was 68.2 ± 12.4 years, i.e. 64.7 ± 10.8 years and 84.3 ± 3.4 years in the younger and the older groups, respectively (p<.001). Atrial fibrillation and pre-stroke anticoagulation among patients over 80 years was more likely (p<0.0005 and p=0.02, respectively). NIHSS scores on admission and at 24 hours were higher in elderly patients (p<0.0001). At three months, 59.8% of the patients from the older group had an unfavourable outcome (p<0.0001), however 34.7% had independent outcome. The one-year- survival was significantly worse in the older group (p<0.0001). The incidence of SICH was lower among older patients. In a logistic regression model, atrial fibrillation, heart failure, diabetes mellitus and smoking were proven as a significant independent risk factors for worse outcome. Conclusion: Although, the outcomes were less favourable in patients over 80 years of age, our results support the feasibility of using intravenous thrombolysis among patients over 80 years of age.